2022
DOI: 10.1088/2053-1591/ac8149
|View full text |Cite
|
Sign up to set email alerts
|

Ortho-atomic projector assisted DFT+U study of room temperature Ferro- and antiferromagnetic Mn-doped TiO2 diluted magnetic semiconductor

Abstract: Using ortho-atomic Hubbard-corrected density functional theory, we present magnetic properties, ferromagnetic transition temperature Tc, Neel temperature TN, electronic structure, structural formation energy, and crystal structure of anatase (Ti16−xMnxO32 for x = 1,2,3,4 and 6). According to the calculated formation energy, an oxygen-rich condition is more structurally stable than a Ti-rich situation. The geometric and lattice parameter optimization result indicates that Mn2+ exists in the system. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…The structure simulation and mechanism analysis have demonstrated the co-doped TiO 2 gas sensor's improved characteristics and excellent gas-sensing capabilities at ambient temperature [131]. An ab initio study of the systems Ti 1−x R x O 2 (R = Mn, Fe, Co, Ni, Cu for various concentrations of substitutional impurities) in the rutile structure revealed that magnetic moments are present in Fe, Co, and Mn but not in Cu or Ni [132,133]. These calculations reveal an essential fact: doping reduces the energy required for vacancies to occur, resulting in doped systems having more vacancies than undoped systems.…”
Section: Quantum Computational Verification Of Experimental Doping Of...mentioning
confidence: 99%
See 2 more Smart Citations
“…The structure simulation and mechanism analysis have demonstrated the co-doped TiO 2 gas sensor's improved characteristics and excellent gas-sensing capabilities at ambient temperature [131]. An ab initio study of the systems Ti 1−x R x O 2 (R = Mn, Fe, Co, Ni, Cu for various concentrations of substitutional impurities) in the rutile structure revealed that magnetic moments are present in Fe, Co, and Mn but not in Cu or Ni [132,133]. These calculations reveal an essential fact: doping reduces the energy required for vacancies to occur, resulting in doped systems having more vacancies than undoped systems.…”
Section: Quantum Computational Verification Of Experimental Doping Of...mentioning
confidence: 99%
“…All dopants significantly stabilize anatase compared to the rutile phase, indicating that the conversion of anatase to rutile is prevented in such systems, with the dopants arranged in the order F > Si > Fe > Al according to the strength of anatase stabilization. The Al and Fe dopants act as shallow acceptors, with charge balance achieved by the formation of mobile charge carriers rather than anion vacancies [133,134,[137][138][139]. In Si-TiO 2 , the Si dopant acts as an inhibitor of the phase transformation from anatase to rutile; in Al-TiO 2 , the Al dopants act as weak inhibitors of the phase transformation from anatase to rutile, and the Fe dopants act as inhibitors of the phase transformation in TiO 2 [133].…”
Section: Quantum Computational Verification Of Experimental Doping Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…Semiempirical approaches, such as DFT + U [24][25][26] and hybrid density functionals (HSE) [27], which were originally developed to improve the description of the ground-state energies of small molecules, have been shown to improve the description of bandgaps in semiconductor systems [28]. Furthermore, the prediction of quasi-particles necessitates the use of many-body techniques, such as the many-body perturbation theory (MBPT) based on the GW method, to describe the energies of solid-state electronic excitation spectra.…”
Section: Introductionmentioning
confidence: 99%